C.S. Parnell, a Controversial Irish Political Leader: A Portrait by Dorothy Eden in her Novel, Never Call it Loving - S. Qasim, Mohammed; A. Sabi, Munthir; R. Hussein, Fatima (Al-Adab Journal, 2019)
Charles Stewart Parnell (1846-91), an Irish political leader of nationalists, causes a national controversy and division by taking Kitty O’Shea, wife of one of his followers, Captain O’Shea, as his mistress. This leads to massive contention between the Irish Catholic Church the nationalist strugglers, who deem him as their own leader and denounce the Church for its involvement in politics. This love story, condemned by the Church as adultery, becomes one of the rarest romances, matched by the famous mad love of Catherine and Heathcliff in Emily Bronte’s Wuthering Heights (1847), as depicted by Dorothy Eden in her novel, Never Call it Loving(1966). Eden is most sympathetic to this estranged wife, Kitty, who falls in love with the most charismatic man, Mr. Parnell; like Heathcliff, Parnell dies miserably, leaving the Irish nation in serious schism. This moving novel is analysed as a sample of historical fiction, which delights readers by its accurate and impressive depiction of this romance; historians can rarely do this, for they’re concerned with mere dry facts.